Chicken NFI/TGGCA proteins are encoded by at least three independent genes: NFI-A, NFI-B and NFI-C with homologues in mammalian genomes. - Rupp, R A (1990)
Chicken TGGCA proteins belong to the ubiquitous, eukaryotic family of NFI-like nuclear proteins, which share an identical DNA binding specificity. They are involved in viral and cellular aspects of transcriptional regulation and they are capable of stimulating Adenovirus initiation of replication. Using microsequencing data from peptides of isolated proteins and PCR supported cloning, we have derived four cDNAs for NFI/TGGCA proteins, which are encoded by three separate chicken genes. Sequence alignments of NFI proteins from chicken and various mammalian species provide evidence for a common genetic equipment among higher eukaryotes, in which several related genes, employing each differential RNA splicing generate an unexpectedly large family of diverse NFI proteins. The extensive similarity of the amino acid sequence throughout the complete coding regions between products of the same gene type in different species indicates a uniform selection pressure on all protein parts, also on those outside the DNA-binding domain.